A Música dos Trigramas e o Balé I Ching de Marco Antônio Guimarães com o UAKTI - Alexandre Campos Amaral Andres (2014)
The Brazilian Uakti Group of instrumental music, formed in 1978 by composer Marco Antônio Guimarães, along with flutist Artur Andrés and percussionists Decio de Sousa Ramos Filho and Paulo Sérgio Santos has developed, for thirty-five years now, innovative work in the fields of instrumental music and construction of new acoustic musical instruments. With twelve worldwide released CDs, Uakti is also engaged in music education, as well as soundtracks for movies and ballet. The I Ching CD, one of the most significant works of the group, has music originally written to be choreographed and was based on the eponymous book I Ching, the book of changes. The eight pieces set A Música dos Trigramas [The Music of the Trigrams] comprise the first part of Marco Antônio Guimarães I Ching and is the main focus of this dissertation. In order to introduce the reader to their musical analysis, the philosophical foundations of the classical Chinese book I Ching will be presented, as well as some aspects of its history and the historical context of the Uakti group.The final goal of this dissertation is to present to the reader the compositional and performance procedures in A Música dos Trigramas, departing from the use of broken and unbroken lines - Yin and Yang used as rhythm figures.